2020
DOI: 10.1136/bmjopen-2020-039258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with overweight and obesity among patients with type 2 diabetes mellitus in Uganda—a descriptive retrospective study

Abstract: ObjectivesTo assess the prevalence and risk factors of overweight and obesity among type 2 diabetes mellitus (T2DM) patients in Uganda.DesignRetrospective chart review.SettingThis study was conducted in the outpatient’s T2DM clinic in St. Francis Hospital—Nsambya, Uganda between March and May 2017.ParticipantsType 2 diabetes patients registered in the diabetes clinic between July 2003 and September 2016.Outcome measuresOverweight and obesity defined as body mass index (kg/m2) of 25.0–29.9 and obesity as 30.0 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…1 Type 2 DM (T2DM) accounts for over 75% of all cases globally; and it's associated with modifiable risk factors such as obesity, unhealthy dietary habits, sedentary life style, alcohol consumption and cigarette smoking. [2][3][4][5] DM is characterized by hyperglycemia, dyslipidemia and disordered immune function that result in micro and macrovascular complications such as peripheral neuropathy, retinopathy, nephropathy, peripheral vascular disease, stroke and coronary artery disease. [6][7][8] Despite advances in DM diagnosis, therapies and supportive management, these complications account for a growing burden of morbidity, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1 Type 2 DM (T2DM) accounts for over 75% of all cases globally; and it's associated with modifiable risk factors such as obesity, unhealthy dietary habits, sedentary life style, alcohol consumption and cigarette smoking. [2][3][4][5] DM is characterized by hyperglycemia, dyslipidemia and disordered immune function that result in micro and macrovascular complications such as peripheral neuropathy, retinopathy, nephropathy, peripheral vascular disease, stroke and coronary artery disease. [6][7][8] Despite advances in DM diagnosis, therapies and supportive management, these complications account for a growing burden of morbidity, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are similar to the Ugandan retrospective study, which reported a high prevalence of overweight and obesity amongst T2DM patients. 32 It has been reported that overweight and obesity amongst patients with diabetes increase burden of disease and poor outcomes. 33 Five longitudinal cohort studies conducted have pointed out that overweight or obese patients with diabetes are at a twofold higher risk of mortality compared with those with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many scholars believe that the shocking increase in DM prevalence in all populations of the world can be attributed to modifiable risk factors such as advanced age, physical inactivity, overweight and obesity, excessive drinking, hypertension, dyslipidaemia and increased urbanisation 11–15. However, the majority of such studies were conducted in African and western countries, where people have different racial and demographic characteristics than Asians.…”
Section: Introductionmentioning
confidence: 99%